Information Technology Management in Learning for Children with Special Needs in Special School - Jesika, Jesika; Hidayati, Dian (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Using technology in daily activities has become common and mandatory so that educational development can compete and provide significant opportunities for special schools to improve education and empower students with special needs. However, there has yet to be any research that reveals the planning and organizing of information technology in special needs learning in special schools, making technology-based learning not optimally implemented and challenging to implement. Therefore, this research was conducted using a qualitative descriptive type, with data collection using the triangulation of data sources based on interviews, documentation, and observation data results. The research informants were the principal, vice principal for curriculum, and teachers at state special schools. The research results obtained are of significant importance as they revealed the management of information technology in special needs learning in special schools, which began with planning, and the organizing stage. These results provide valuable insights and recommendations for the effective management of information technology in special needs learning in special schools, addressing the current challenges.